Peran Psikologi dalam Pendidikan Islam - Al Faizi, Ahmad Akbar; Murtadho, Imam (Lembaga Yasin AlSys, 2025)
This study aims to examine the role of psychology in Islamic education by highlighting the integration of psychological principles into the learning process to enhance the effectiveness of education rooted in Islamic values. A qualitative approach was employed using the library research method, analyzing literature related to educational psychology and Islamic education. The findings reveal that psychology plays a crucial role in understanding student characteristics, designing learning methods aligned with developmental stages, and shaping holistic personalities encompassing cognitive, affective, and psychomotor domains. In the context of Islamic education, the application of psychological principles supports the internalization of moral values, enhances learning motivation, and guides spiritual development. The integration of psychology and Islamic education provides a foundation for implementing holistic education aimed at nurturing insan kamil—a complete human being in both intellectual and spiritual dimensions. Thus, the synergy between these two disciplines serves as a critical basis for developing an educational system that fosters not only academic excellence but also strong character and morality.